Struggles for Equal Voice : The History of African American Media Democracy - Kiuchi, Yuya (Book collections on Project MUSE., 2012)
This book reveals how African Americans have utilized access to cable television production and viewership as a significant step toward achieving empowerment during the post-Civil Rights and Black Power era[s]. -- Page 4 of cover.